ANALISIS TINGKAT KEPUASAN NASABAH BANK, PENERAPANMETODEANALYTICAL HIERARCHY PROCESS - Arlian, Ujang; Lestari, Etty Puji (LPPM Universitas Terbuka, 2015)
The development of the banking industry continues to progress over time. History has recorded that the banking industry advances occur after the deregulation package. Impact after the deregulation package that is increasing the number of private banks in Indonesia.Both private banks and state banks/enterprises vying to attract customers. Regional Development Bank (BPD), which has changed its name to the name of the province in Indonesia is also trying to implement a variety of strategies to encourage people to do deposits. The purpose of this study is to determine the level of satisfaction of bank customers who are in Lebong. The analytical method used is Analytical Hierarchy Process (AHP). Using four (4) criteria such as facilities, products, services, and security as a comparison between the two banks. The results showed that the criteria for the facility is a major factor in determining the level of customer satisfaction.Then followed the safety criteria for second place while the third and fourth position are the criteria of products and services.  Perkembangan industri perbankan terus mengalami kemajuan dari waktu ke waktu. Sejarah telah mencatat bahwa kemajuan industri perbankan terjadi setelah masa paket deregulasi. Dampak setelah masa paket deregulasi yaitu bertambah banyaknya bank swasta di Indonesia. Baik bank swasta maupun bank BUMN/BUMD berlomba-lomba untuk menarik nasabah. Bank Pembangunan Daerah (BPD) yang telah berubah nama menjadi nama provinsi di Indonesia juga berupaya dengan menerapkan berbagai strategi untuk mengajak masyarakat melakukan simpanan. Tujuan penelitian ini yaitu untuk mengetahui tingkat kepuasan nasabah perbankan yang terdapat di Kabupaten Lebong. Metode analisis yang digunakan adalah Analytical Hierarchy Process (AHP). Menggunakan 4 (empat) kriteria seperti fasilitas, produk, pelayanan, dan keamanan sebagai pembanding diantara kedua bank tersebut. Hasil penelitian menunjukkan bahwa kriteria fasilitas merupakan faktor utama didalam menentukan tingkat kepuasan nasabah. Kemudian disusul kriteria keamanan diposisi kedua sedangkan diposisi ketiga dan keempat ialah kriteria produk dan pelayanan.